Evaluation of cytomegalovirus infection/disease in IgG positive renal transplantation recipients on valaciclovir prophylaxis - Sari, Tugba; Dursun, Belda; Ceri, Mevlut; Ergin, Cagri; Turgut, Huseyin; Ozban, Murat (The Journal of Infection in Developing Countries, 2022)
Introduction: The reactivation of CMV (Cytomegalovirus) in renal transplant recipients may be manifested across a clinical spectrum from asymptomatic viraemia to organ rejection. The purpose of this study is to evaluate the patients who have experienced CMV infection after renal transplantation in the last twelve years, and to assess the efficacy of valacyclovir. Methodology: Renal transplant recipients’ demographic, clinical and laboratory data were evaluated retrospectively between 2006-2018. Valaciclovir was given at the standard prophylaxis dose of 2000 mg/daily. CMV Polymerase Chain reaction (PCR) was performed in 2-week intervals until 1 year after transplantation, and upon any symptoms attributable to CMV. Results: The entire study group had D+/R+ (donor–positive, recipient-positive) serological status of the CMV virus. 171 (59.2%) patients had only CMV infection, 60 (20.8%) had overall CMV antigen positivity until the end of the follow-up period and 7 (2.4%) patients had CMV disease. Rejection episodes were diagnosed in 31 (10.8%) patients; 20 (64.5%) of those were PCR positive for CMV; mortality rate was 12 (4.2%) but those who died had a non-CMV related disease. Conclusions: Valaciclovir may be preferred in prophylaxis instead of valganciclovir as we used in our study since valganciclovir has prolonged treatment time, rapid development of drug resistance, drug toxicity and high cost.